A new HWWA raw material price index - H. -J. Timm (Intereconomics, 1980)
In this place we regularly published the HWWA Index of World Market Prices which has been computed since the fifties and was a comprehensive indicator of the price movements of the major raw materials traded in the world markets. Unavoidably, an, index of this kind has to be adjusted from time to time to allow for changes in the pattern of world trade. Such an adjustment has just been completed. For a better understanding and use of the new index by our readers in the future the following explanation should serve.
Keywords: 330; Economic Trends